FAKTOR YANG MEMPENGARUHI MINAT LULUSAN SMK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DI KECAMATAN KAMIPANG - Rinto Alexandro; Tonich Uda; Merisa Oktaria; Windy Utami Putri (JURNAL PENDIDIKAN, 2021)
The results of the study showed that there was a positive influence of economic factors, socio-cultural factors and environmental factors on the interest of SMK graduates to continue their education to Higher Education. The higher the economic factor, socio-cultural and environmental factors affect the interest of SMK graduates to continue their education to Higher Education, the lower the interest of SMK graduates to continue their education to Higher Education in Kamipang District, Katingan Regency. There is a very strong relationship between economic factors, socio-cultural factors and environmental factors on the interest of SMK graduates to continue their education to Higher Education with a multiple correlation value of 0.88. There is a partial significant influence of economic factors and socio-cultural factors on the interest of SMK graduates to continue their education to higher education in Kamipang District, Katingan Regency. Meanwhile, partially environmental factors have no effect on the interest of vocational school graduates to continue their education to higher education in Kamipang District, Katingan Regency. With the partial influence of economic factors of 30%, socio-cultural factors of 41.85%, and environmental factors of 4.65% And economic factors, socio-cultural factors and environmental factors together have a significant influence on the interest of SMK graduates to continue education to college.